2020
DOI: 10.4328/acam.6210
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based survey on the pattern of eye diseases in Arar, Saudi Arabia

Abstract: Aim: In this study we aimed to evaluate the pattern of eye diseases (PED) in people attending a government hospital in Arar city of Saudi Arabia. Material and Method: This study was carried out on 1238 people visiting the eye out patient department (OPD) of Arar Central Hospital. Anterior and posterior segment eye examination was done to diagnose the eye diseases and treat them accordingly. Results: A total of 620 (50.1%) males and 618 (49.9%) females were enrolled in the current study whose ages ranged from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…7,8 Ironically almost all of these causes are potentially preventable and or easily treatable, but the bulk of the victims in Africa and Asia are either too poor, ignorant or do not have eye-care services available to them. Parrey et al 9 conducted a study and reported that the commonest ocular morbidity as conjunctivitis (31.7%) followed by refractive error, cataract, diabetic retinopathy and strabismus in 20.9%, 14.8%, 8% and 3.1% cases, respectively. In an another study, Parrey et al 10 performed another study and reported that cataract was found to be the main cause of visual impairment (30.7%) followed by refractive error (24.7%) and diabetic retinopathy (13.2%).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Ironically almost all of these causes are potentially preventable and or easily treatable, but the bulk of the victims in Africa and Asia are either too poor, ignorant or do not have eye-care services available to them. Parrey et al 9 conducted a study and reported that the commonest ocular morbidity as conjunctivitis (31.7%) followed by refractive error, cataract, diabetic retinopathy and strabismus in 20.9%, 14.8%, 8% and 3.1% cases, respectively. In an another study, Parrey et al 10 performed another study and reported that cataract was found to be the main cause of visual impairment (30.7%) followed by refractive error (24.7%) and diabetic retinopathy (13.2%).…”
Section: Discussionmentioning
confidence: 99%
“…When all age groups were included, they showed that the most common diagnoses in the eye clinics were conjunctivitis (31.7%), refractive errors (20.9%), and cataracts (14.8%). [ 3 ] In younger age groups, the most common ophthalmic morbidities were strabismus (36.9%), refractive errors (26.5%), and conjunctival/corneal infections (7.3%). [ 4 ]…”
Section: Introductionmentioning
confidence: 99%